Fish Exhibit Distinct Fluorochemical and δ15N Isotopic Signatures in the St. Lawrence River Impacted by Municipal Wastewater Effluents - Kaboré, Hermann A.; Goeury, Ken; Desrosiers, Mélanie; Vo Duy, Sung; Liu, Jinxia; Cabana, Gilbert; Munoz, Gabriel; Sauvé, Sébastien (Frontiers in Environmental Science, 2022)
We examined the influence of Montreal wastewater treatment plant (WWTP) effluents on two top predators, Walleye (Sander vitreus) and Sauger (Sander canadensis), with a focus on δ15N isotopic signatures and per- and polyfluoroalkyl substances (PFAS). These two fish species were collected in the summer 2013 in the St. Lawrence River upstream and downstream from a major WWTP, as well as in background sites (semi-remote lakes). Most of the δ15N variations for Sauger and Walleye are attributable to 1) δ15N values of the primary producers and sewage-derived particulate organic matter (SDPOM) at the base of the trophic food chain, 2) agricultural activities combined with biogeochemical processes, and 3) food web length. δ15N was significantly lower in fish collected in the effluent-mixed water masses than other sites of the St. Lawrence River, attributed to the SDPOM of the WWTP effluent. Relative to the background sites, certain PFAS were present at much higher levels in the St. Lawrence River, with profiles dominated by perfluoroalkyl sulfonates (PFSA). However, PFSA profiles generally remained consistent along the St. Lawrence River. PFOS levels in fish from the St. Lawrence exceeded the current Federal Environmental Quality Guidelines for protecting piscivorous mammals or birds. However, the human chronic daily intake of PFOS remained below current thresholds suggested by national agencies.